2012
DOI: 10.5888/pcd9.110015
|View full text |Cite
|
Sign up to set email alerts
|

Interventions in Small Food Stores to Change the Food Environment, Improve Diet, and Reduce Risk of Chronic Disease

Abstract: IntroductionMany small-store intervention trials have been conducted in the United States and other countries to improve the food environment and dietary behaviors associated with chronic disease risk. However, no systematic reviews of the methods and outcomes of these trials have been published. The objective of this study was to identify small-store interventions and to determine their impact on food availability, dietary behaviors, and psychosocial factors that influence chronic disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
316
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(337 citation statements)
references
References 35 publications
13
316
3
5
Order By: Relevance
“…Essas iniciativas poderão incentivar o consumo de alimentos considerados saudáveis como alimentos integrais, frutas, legumes e verduras ricos em vitaminas, minerais e fibras e com baixo teor de gorduras e sal, propiciando escolhas alimentares mais saudáveis e, consequentemente, menores riscos de desenvolvimento de DCNT, com destaque para o sobrepeso/obesidade na população escolar. Ações similares já foram desenvolvidas em outros estudos com resultados significativamente positivos 42,43,44 .…”
Section: Discussionunclassified
“…Essas iniciativas poderão incentivar o consumo de alimentos considerados saudáveis como alimentos integrais, frutas, legumes e verduras ricos em vitaminas, minerais e fibras e com baixo teor de gorduras e sal, propiciando escolhas alimentares mais saudáveis e, consequentemente, menores riscos de desenvolvimento de DCNT, com destaque para o sobrepeso/obesidade na população escolar. Ações similares já foram desenvolvidas em outros estudos com resultados significativamente positivos 42,43,44 .…”
Section: Discussionunclassified
“…En general, se ha obtenido un impacto modesto en composición corporal (19) . Intervenciones aisladas en la comunidad, enfocadas en incrementar opciones saludables de alimentos en bodegas, o mejorar la infraestructura disponible en la comunidad para realizar actividad física, no han tenido resultados muy alentadores (20) ; sin embargo, los resultados podrían mejorar si las intervenciones en la comunidad se desarrollan con participación de la población general en su implementación, o si se asocian a intervenciones escolares (21) . Sin duda, este tipo de intervenciones necesitan una mayor exploración y constituyen una importante área de expansión dentro de las actividades para combatir la obesidad infantil.…”
Section: Lecciones Aprendidas De Intervenciones Para Combatir La Obesunclassified
“…grocery store and corner store interventions) are increasingly recognized as important public health interventions to improve the nutritional quality of food purchases. [1][2][3][4] Such interventions aim to support healthier dietary behaviours by improving access to and availability of affordable, nutritious food options in the community and consumer nutrition environments. 5,6 Food stores are especially important sites for healthy eating interventions, since over 70 cents of every household food dollar is spent in stores (as opposed to restaurants).…”
Section: Introductionmentioning
confidence: 99%
“…3 Another 2012 review that examined impacts of retail interventions in small food stores found the majority of studies (11 of 16 evaluations) did not analyze sales data. 2 Only a few studies have used sales data to assess retail performance of the store as the primary outcome of interest. 18 There are many reasons why previous research has not used sales data, including the potentially sensitive nature of the data, and its poor quality due to human error or technological barriers.…”
Section: Introductionmentioning
confidence: 99%